Slumming: Sexual and Social Politics in Victorian London - Gorham, Deborah (Labour / Le Travail, 2006)
The article reviews the book, "Slumming: Sexual and Social Politics in Victorian London," by Seth Koven.
Keywords: BOOKS – Reviews; KOVEN; Seth; Nonfiction; SEX customs; SLUMMING: Sexual & Social Politics in Victorian London (Book)